Os níveis de desenvolvimento socioeconômico da população da Amazônia brasileira: 1970 e 1980 Levels of socioeconomic development in the Brazilian Amazon: 1970 and 1980 - Archibald O. Haller; Ramon S. Torrecilha; Maria Cristina del Peloso Haller; Manoel M. Tourinho (História, Ciências, Saúde: Manguinhos, 2000)
O artigo discute uma tipologia das áreas de fronteira na Amazônia brasileira e a relevância do conceito de fronteira para o estudo da emergência de anomia social nessas áreas. Propõe correlação positiva entre mudança social acelerada e fatos sociais anômicos, diluição de famílias, criminalidade, violência etc. Apresenta escores dos níveis de desenvolvimento socioeconômico per capita (DSE/kmu) das populações de todos os municípios da Amazônia Legal para 1970 e 1980, e conclui que os escores de 327 dos 329 municípios estudados cresceram, o que indica a melhora das condições de vida da população regional, contradizendo a hipótese, comum na literatura, de disrupção social na Amazônia brasileira. Assim, a anomia deve ser esperada com a mudança acelerada. Fatos anômicos não desmentem as melhoras socioeconômicas. The text presents a typology of the different frontier areas within the Brazilian Amazon today and discusses the relevance of the concept of frontier in studying the emergence of social anomie in those areas. It suggests there is a positive correlation between the processes of accelerated social change characteristic of such areas and signs of social anomie, such as the loosening of family and personal ties, increased crime and violence, deterioration of the public order, etc. Per capita levels of socioeconomic development (DSE/kmu) were measured among people residing in all municipalities within the administrative region known as Amazônia Legal, for 1970 and 1980. Growth in the scores of 327 of the 329 municipalities under study indicates a strong trend towards improvement of living conditions for the region’s residents. This contradicts the hypothesis found in most of the analytical literature, which contends that the Brazilian Amazon has been stage to social disruption or stagnation. The text argues that anomie is to be expected in situations of accelerated social change, where people, values, and identities are unstable. Therefore, evidence of anomie, which confirms the occurrence of changes, cannot be used to negate the socioeconomic improvements observed in the Brazilian Amazon.